8.4 Serum beta defensin concentration in the first trimester is related to genotype, and is higher in women who develop PPROM and deliver before 34 weeks. (9th June 2014) - James, CP; Bajaj-Elliott, M; Syngelaki, A; Klein, N; Nicolaides, K; Peebles, DM
Abstract : Background: Previously we showed that the DEFB1 SNP rs1799946 is associated with PPROM and a four-fold increase in spontaneous preterm birth risk (PTB); rs1047031 may reduce the risk of PTB. This study describes the relationship between DEFB1 genotype, its constituent human beta defensin 1 (hBD1) protein expression and clinical phenotype, and the expression of inducible human beta defensin 2 (hBD2). Methods: Blood was collected at 11–13/40 (n = 400, King's College Hospital 2006–2010) and genotyped for rs1799946 and rs1047031 using KASP (Kompetitive Allele Specific PCR). Serum hBD1 and hBD2 concentrations were determined by ELISA (n = 292). Analyses were by Kruskal-Wallis and Mann-Whitney-U tests. Results: rs1047031 is associated with lower serum hBD1 concentration (p = 0.0200), and rs1799946 with a trend to increased hBD1 concentration (p = 0.0264). Of 292 women with serum samples, 59 delivered <34/40 (28 PPROM, 31 spontaneous). Women with PPROM and PTB <34/40 had higher hBD1 concentrations than those delivering at term (1.15MoM, IQR 0.753–2.12 vs 0.995MoM, IQR 0.739–1.34). Serum hBD1 concentration was negatively correlated with mid-gestation cervical length (r = –0.170, 95%CI –0.326–0.00532, p = 0.0433). Similarly, serum hBD2 concentration is higher in pregnancies with PPROM and PTB <34/40 compared to term birth (1.51MoM, IQR 0.75–3.47, vs 0.94MoM, IQR 0.511–1.55, p = 0.0116). Conclusion: DEFB1 genotype is related to serum hBD1 expression in the first trimester and clinical phenotype. Serum hBD2 expression is higher in women who have PPROM and PTB. Women with PPROM and PTB have a distinct innate immune profile evident in their serum in the first trimester, which may provide the basis for a predictive test.